2004
DOI: 10.1677/erc.0.0110117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of androgen receptor signalling via steroid receptor coactivator-1 in prostate.

Abstract: The androgen receptor (AR) is a member of the nuclear receptor superfamily. These ligand-activated transcription factors usually contain two activation functions, a ligand-independent activation function 1(AF1) in the divergent N-terminal domain and a ligand-dependent AF2 in the more conserved Cterminal ligand-binding domain. To promote transcription from target promoters, DNA-bound nuclear receptors recruit coactivator proteins that promote transcription by modifying histones within nucleosomes, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 75 publications
4
39
0
1
Order By: Relevance
“…A previous study of DRG1 regulation in LNCaP cells also showed high specificity for androgens, although in this case SARMs were not studied (Ulrix et al, 1999). This all adds to a growing body of evidence supporting the notion that differential expression of steroid target genes is dependent upon many factors including the promoter, receptor interactions (both intra-receptor and with other proteins) and post-translational modifications (He et al, 2002;Li et al, 2003;Callewaert et al, 2004;Powell et al, 2004). The implications go beyond differential expression of androgen-responsive genes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A previous study of DRG1 regulation in LNCaP cells also showed high specificity for androgens, although in this case SARMs were not studied (Ulrix et al, 1999). This all adds to a growing body of evidence supporting the notion that differential expression of steroid target genes is dependent upon many factors including the promoter, receptor interactions (both intra-receptor and with other proteins) and post-translational modifications (He et al, 2002;Li et al, 2003;Callewaert et al, 2004;Powell et al, 2004). The implications go beyond differential expression of androgen-responsive genes.…”
Section: Discussionmentioning
confidence: 82%
“…Both SRC-1 and ARA70 are expressed in human prostate cancer cell lines and in normal prostate, in the luminal epithelial cells that also express AR (Gregory et al, 2001;Linja et al, 2001;Hu et al, 2004;Powell et al, 2004;Agoulnik et al, 2005). There is both in vitro and in vivo evidence that SRC-1 is required for optimal androgen signalling and growth in the prostate, since knockdown of SRC-1 attenuated growth and androgendependent gene expression in androgen-sensitive prostate cancer cell lines (Agoulnik et al, 2005), and SRC-1-null mice exhibit attenuation of androgenstimulated prostatic growth (Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The ligand-binding domain, where androgens bind, results in a conformational change in the AR, where it dissociates from heat shock proteins in the cytoplasm, and localizes to the nucleus (13 ). In the nucleus, the AR binds to specific DNA sequences, called androgen responsive elements, via the DNA-binding domain, promoting further association of factors into a complex, which leads to gene transcription (14 ). Various genes are regulated by the AR, including kallikrein-related peptidase 3 (KLK3), 6 which encodes kallikrein-3 (formerly known as prostate-specific antigen), one of the best cancer biomarkers available.…”
Section: Androgen Receptor Signaling: a Key Regulator Of Prostate Canmentioning
confidence: 99%
“…Coactivator proteins are recruited to a ligandbound receptor and thereby enhance its transcriptional activity (Powell et al 2004). So far, there are 300 known coactivators for nuclear receptors, including nuclear receptor coactivator 1 (NCOA1/SRC1), which is a member of the p160 nuclear receptor coactivator family.…”
Section: Introductionmentioning
confidence: 99%
“…NCOA1 acts as a scaffold protein that houses a central nuclear receptor-interacting domain and two activation domains, which are located at the carboxy-terminus and flank a glutamine-rich region. This glutamine-rich region interacts with the amino-terminal part of the AR (Powell et al 2004). …”
Section: Introductionmentioning
confidence: 99%